Application of STORET Method to Determine Lake Sentani Water Quality Status in Papua Province - Suyatno Suyatno; Bambang Suhartawan; Santje M. Iriyanto; Daawia Daawia (Publikasi Indonesia, 2024)
Lake coastal communities utilize Lake Sentani's water to meet clean and other needs such as industry, irrigation, plantations, fisheries, and water transportation facilities. In addition to the lake mentioned above, they use it as a garbage dump and family waste; even human and animal feces are thrown into Lake Sentani. This study aims to determine the quality and quality status using the STORET method based on PP 22 of 2021 concerning the Implementation, Protection, and Management of the Environment annex vi-2 class 1 by applying ten parameters. The study used three stations: Ifale, Asei, and Jaifuri coast. Each station was sampled four times: January, April, July, and October 2023. The results showed that seven parameters did not meet the quality standards, namely TSS, BOD, COD, Pb, Oil and Fat, Total Ditergen, and Total coliform, and only three parameters met the quality shoulder, namely temperature, TDS, and pH. Water quality status based on the application of the STORET method was obtained that station 1 obtained a score of -26 based on US_EPA, including class C (moderately polluted), station 2 obtained a score of -64, including class D (heavily polluted), and station 3 obtained a score of -116 including class D (heavily polluted) and the average STORET score of the three stations was obtained -68.67 including class D (heavily polluted).